2014
DOI: 10.1088/0953-2048/27/12/125010
|View full text |Cite
|
Sign up to set email alerts
|

Critical state solution of a cable made of curved thin superconducting tapes

Abstract: In this paper we develop a method based on the critical state for calculating the current and field distributions and the AC losses in a cable made of curved thin superconducting tapes. The method also includes the possibility of considering spatial variation of the critical current density, which may be the result of the manufacturing process. For example, rare-earth based coated conductors are known to have a decrease of the transport properties in near the edges of the tape: this influences the way current … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…[701] The reason for this is that in power transmission cables, superconducting tapes are wrap around a cylindrical former and the tapes can be curved conforming the shape of the cylinder. [655,664] In particular, theoretical investigations revealed that bending a superconducting tape leads to a reduction of the magnetic field acting perpendicular to the tape that has been suggested as a route to reduction of ac losses. [654,655] For a thin-film superconducting tubular wire, analytical expressions for the magnetic-field and current distributions have been obtained [661] and timedependent electric fields with a trapped vortex have been shown to be very similar to the ones exhibited by resistively shunted Josephson junctions.…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…[701] The reason for this is that in power transmission cables, superconducting tapes are wrap around a cylindrical former and the tapes can be curved conforming the shape of the cylinder. [655,664] In particular, theoretical investigations revealed that bending a superconducting tape leads to a reduction of the magnetic field acting perpendicular to the tape that has been suggested as a route to reduction of ac losses. [654,655] For a thin-film superconducting tubular wire, analytical expressions for the magnetic-field and current distributions have been obtained [661] and timedependent electric fields with a trapped vortex have been shown to be very similar to the ones exhibited by resistively shunted Josephson junctions.…”
Section: State Of the Artmentioning
confidence: 99%
“…[655,664] In particular, theoretical investigations revealed that bending a superconducting tape leads to a reduction of the magnetic field acting perpendicular to the tape that has been suggested as a route to reduction of ac losses. [654,655] For a thin-film superconducting tubular wire, analytical expressions for the magnetic-field and current distributions have been obtained [661] and timedependent electric fields with a trapped vortex have been shown to be very similar to the ones exhibited by resistively shunted Josephson junctions. [657] Curved thin sub-micrometer-sized stripes conforming to cylindrical shells have been theoretically investigated with emphasis on nucleation [660] and thermal activation [659] of phase-slip lines.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation